Bus-Based VANET using ACO Multipath Routing Algorithm - Dhaya, R.; Kanthavel, R. (Journal of Trends in Computer Science and Smart Technology, 2021)
Vehicular ad-hoc Network (VANET) for buses provides a good solution with inconsistent and high dynamic structure of a typical network. In this work, Street-centric routing algorithm is used for internet of energy for the bus-based VANET to optimize relay bus and route selection issues. As the initial step, we have used a multipath routing system that uses probability of path consistency and street consistency. This methodology is observed to positively improve end-to-end delay and also the packet delivery ratio. The next step is to optimize the characteristics of packet forwarding by means of an Ant Colony Optimization (ACO) methodology as the mechanism for relay-bus selection. The main goal of this paper is to transmit packets to the next forwarding relay with the help of relay-bus. On experimental analysis, the results indicate that there is a significant improvement in relay-bus choosing by reducing the end-to-end delay, cost of computation and unwanted beacon messages. Based on the analysis, we have arrived at the conclusion that the use of clustering and multipath will positively improve the performance of the proposed work.
Keywords: internet of energy; relay selection; multipath routing; clustering; Ant Colony Optimization